Hareios Poter: um estudo descritivo sobre a tradução dos nomes próprios de Harry Potter and the Philosopher’s Stone para o grego antigo - Bezerra, João Alfredo Ramos (2017)
With undeniable repercussion, the Harry Potter books were published between the years of 1997 and 2007, totaling seven titles. Although one of the largest literary phenomenon in the beginning of the XXI century, the series tend not to be given proper look by the academic community because it is a best-seller classified as children’s literature. Even though, few academic questions rise timidly, such as translation issues, since the books have different lexicon, complex plot, and not common extension for this genre. The study of proper names, known as Onomastics, are part of a specific group, once many of them are puns or have implicit meaning which may go underway depending on the translation procedure. Due to success and expressive numbers, the books are the epicentre in a web of translations. Among so many versions, the first book, Harry Potter and the Philosopher’s Stone (1997), was translated into Ancient Greek in 2004 by British Classical Studies Professor Andrew Wilson. Therefore, the goal in this present study is to compare and analyze the translation of proper names on the mentioned translation through the creation of a list of proper names in English and Ancient Greek, splitting them into categories, observing the translation procedures, the paths chosen by the translator. This way, it is characterized as a descriptive study, based upon Lambert’s and Van Gorp’s method (1985). Initial hypothesis is that these names, especially the ones created by the author, were just transliterated, because it seems easier just to go from the Latin alphabet to the Greek one. To set the list, the book in English, seen here as source text, was read highlighting all proper names by chapter order. By the end of the first stage, the same process was made with the Ancient Greek edition. With the list set, categories of names had to be chosen, such as characters, places, objects, among others. The second stage consisted on setting the translational procedures. With all considered, analysis could be initiated, showing results like which procedures had been used most by the translator. It is concluded then that the translator chose paths like approximating the text to the reader, such as using acoustic approximation, disproving initial hypothesis about the use of transliteration. This way, he showed undue creativity by his choices by making a flowing text.